Exploration of Human Salivary Microbiomes—Insights into the Novel Characteristics of Microbial Community Structure in Caries and Caries-Free Subjects - Zhou, Jianye; Jiang, Nan; Wang, Shaoguo; Hu, Xiaopan; Jiao, Kangli; He, Xiangyi; Li, Zhiqiang; Wang, Jizeng (PloS one, 2016)
Recently, high-throughput sequencing has improved the understanding of the microbiological etiology of caries, but the characteristics of the microbial community structure in the human oral cavity with and without caries are not completely clear. To better understand these characteristics, Illumina MiSeq high-throughput sequencing was utilized to analyze 20 salivary samples (10 caries-free and 10 caries) from subjects from the same town in Dongxiang, Gansu, China. A total of 5,113 OTUs (Operational Taxonomic Units, 97% cutoff) were characterized in all of the salivary samples obtained from the 20 subjects. A comparison of the two groups revealed that (i) the predominant phyla were constant between the two groups; (ii) the relative abundance of the genera Veillonella, Bifidobacterium, Selenomonas, Olsenella, Parascardovia, Scardovia, Chryseobacterium, Terrimonas, Burkholderia and Sporobacter was significantly higher in the group with caries (P < 0.05); and (iii) four genera with low relative abundance (< 0.01% on average), including two characteristic genera in caries (Chryseobacterium and Scardovia), significantly influenced the microbial community structure at the genus and OTU levels. Moreover, via co-occurrence and principal component analyses, the co-prevalence of the pathogenic genera was detected in the caries samples, but in the caries-free samples, the function of clustered genera was more random. This result suggests that a synergistic effect may be influencing the assembly of the caries microbial community, whereas competition may play a more dominant role in governing the microbial community in the caries-free group. Our findings regarding the characteristics of the microbial communities of the groups with and without caries might improve the understanding of the microbiological etiology of caries and might improve the prevention and cure of caries in the future.